2014
DOI: 10.2136/sssaj2014.05.0195
|View full text |Cite
|
Sign up to set email alerts
|

Soil Accretion Influenced by Elevation, Tree Density, and Substrate on Reconstructed Tree Islands

Abstract: Tree islands provide a relatively dry habitat for flora and fauna and are biogeochemical hotspots within the oligotrophic Everglades' marsh. Tree islands occupy a small percentage of Everglades' surface area, yet they provide critical ecosystem functions. Hydrologic manipulations throughout the 20th century resulted in a significant loss of tree islands. This study was conducted to determine previously unknown characteristics of soil development important to creating self‐sustaining tree islands. Physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Tree islands are nutrient hotpots, having 6-100 times more phosphorus than the surrounding P-limited marshes and sloughs (Noe, Childers, & Jones, 2001;Wetzel et al, 2005). Evidence suggests there is a persistent groundwater head gradient toward the tree islands from the surrounding marsh because of specific yield differences and evapotranspiration gradients between the two habitats (Rodriguez, Serna, & Scinto, 2014;Ross et al, 2006). Localized nutrient enrichment on tree islands is also plausibly attributable to animal movement, particularly nesting by wading birds (Givnish et al, 2008;Wetzel et al, 2005).…”
Section: Box 1 Tree Islands In the Everglades Flmentioning
confidence: 99%
“…Tree islands are nutrient hotpots, having 6-100 times more phosphorus than the surrounding P-limited marshes and sloughs (Noe, Childers, & Jones, 2001;Wetzel et al, 2005). Evidence suggests there is a persistent groundwater head gradient toward the tree islands from the surrounding marsh because of specific yield differences and evapotranspiration gradients between the two habitats (Rodriguez, Serna, & Scinto, 2014;Ross et al, 2006). Localized nutrient enrichment on tree islands is also plausibly attributable to animal movement, particularly nesting by wading birds (Givnish et al, 2008;Wetzel et al, 2005).…”
Section: Box 1 Tree Islands In the Everglades Flmentioning
confidence: 99%
“…The species is found in fresh and brackish water, but sporadic high salinity events could induce salt stress in this plant and affect its growth and establishment. Sporadic salinity can occur due to elevation difference from natural saline systems such as the ocean, and such prolonged flooding can have a direct influence on plant survival [15]. Various studies have shown that V. americana can tolerate 5.0 to 15.0 parts per thousand (ppt) salinity [8].…”
Section: Introductionmentioning
confidence: 99%
“…The species is found in fresh and brackish water, but sporadic high salinity events could induce salt stress in this plant and affect its growth and establishment. Sporadic salinity can occur due to elevation difference from natural saline systems such as the ocean, and such prolonged flooding can have a direct influence on plant survival [11]. Various studies have shown that V. americana can tolerate 5.0 to 15.0 parts per thousand (ppt) salinity [8].…”
Section: Introductionmentioning
confidence: 99%